Risperidone-induced extrapyramidal side effects: is the need for anticholinergics the consequence of high plasma concentrations?. (September 2016) - Schoretsanitis, Georgios; Haen, Ekkehard; Hiemke, Christoph; Gründer, Gerhard; Stegmann, Benedikt; Schruers, Koen R.J.; Veselinovic, Tanja; Lammertz, Sarah E.; Paulzen, Michael
Abstract : Antipsychotic drugs can induce various undesirable adverse motor reactions, such as extrapyramidal side effects (EPS). A widely accepted pharmacodynamic mechanism underlying EPS includes an increase in striatal D2 -receptor occupancy. However, less is known about the pharmacokinetic background of EPS. The aim of this study was to analyze in-vivo possible pharmacokinetic patterns underlying biperiden-treated EPS in risperidone (RIS)-medicated patients. A large therapeutic drug monitoring database containing plasma concentrations of RIS and its metabolite 9-hydroxyrisperidone (9-OH-RIS) of 2293 adult inpatients and outpatients was analyzed. Two groups were compared: a group receiving RIS ( n =772) and a group comedicated with biperiden ( n =68). Plasma concentrations, dose-adjusted plasma concentrations (C/D) of RIS, 9-OH-RIS, and active moiety (AM) (RIS+9-OH-RIS) as well as ratios of concentrations for metabolite to parent drug (9-OH-RIS/RIS) were computed. We compared the plasma concentrations of the different compounds between the two groups considering the prescription of biperiden as an indirect report of EPS. The daily dosage of RIS did not differ between groups. No differences were detected in case of plasma concentrations and C/D of RIS and active metabolite between the groups. However, plasma concentrations of the AM were significantly higher in the comedicated group ( P =0.032) and showed a trend in terms of the active metabolite 9-OH-RIS ( P =0.053). Data indicate enhanced AM plasma concentrations of RIS in patients comedicated with biperiden as an EPS treatment. This might underscore an association between higher plasma concentrations of the AM and treatment-requiring EPS.